2010
DOI: 10.4037/ajcc2009541
|View full text |Cite
|
Sign up to set email alerts
|

Sedation Management in Australian and New Zealand Intensive Care Units: Doctors’ and Nurses’ Practices and Opinions

Abstract: Objective To explore the use of sedatives and analgesics, tools for scoring level of sedation, sedation and pain protocols, and daily interruptions in sedation in Australian and New Zealand intensive care units and to examine doctors' and nurses' opinions about the sedation management of critically ill patients. Methods A cross-sectional Internet-based survey design was used. In total, 2146 members of professional critical care organizations in Australia and New Zealand were e-mailed the survey during a 4-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 56 publications
4
55
1
Order By: Relevance
“…[14] In two studies (one of which was a multinational survey conducted by Soliman et al with 647 intensive care physicians and the other conducted by O'Connor et al on sedation usage during MV) it was reported that the most frequently used sedative agents were midalozam and propofol, respectively. [15,16] In our study, the sedative most frequently used in intubated patients was midazolam, followed by diazepam in frequency of use. We also found that if two medicines were used together as sedative agents, the most frequent combination was midazolam and propofol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] In two studies (one of which was a multinational survey conducted by Soliman et al with 647 intensive care physicians and the other conducted by O'Connor et al on sedation usage during MV) it was reported that the most frequently used sedative agents were midalozam and propofol, respectively. [15,16] In our study, the sedative most frequently used in intubated patients was midazolam, followed by diazepam in frequency of use. We also found that if two medicines were used together as sedative agents, the most frequent combination was midazolam and propofol.…”
Section: Discussionmentioning
confidence: 99%
“…In both the study of O'Connor et al [16] and the multinational study of Arroglia et al [14] it was reported that the most frequently used analgesic agents during MVM were morphine sulfate and alfentanyl. Similarly, in our study we found out that fentanyl was the most frequently used, while morphine sulfate was the second most frequently used analgesic agent.…”
Section: Discussionmentioning
confidence: 99%
“…65 Inclusion of sedation in the checklist provides a reminder to nurses to consider progression through sedation protocols, 65 reflect on the appropriateness of current sedation strategies, 64,69 and assess patients for symptoms of tolerance or withdrawal [70][71][72] by using a validated tool when available (eg, Withdrawal Assessment Tool 73 ). The aim of this element is to reduce inappropriate levels of sedation and facilitate early recognition and treatment of the adverse effects associated with sedation.…”
Section: Reference Results Designmentioning
confidence: 99%
“…The main indications for use of sedatives include reducing anxiety and agitation, inducing amnesia, facilitating mechanical ventilation, preventing displacement of endotracheal tubes, and reducing cellular metabolism. [64][65][66][67][68] The consequences of prolonged use of sedative agents in the PICU www.ajcconline.org Pressure injuries remain a common problem in critically ill infants and children.…”
Section: Sedationmentioning
confidence: 99%
“…Th e use of daily interruption for patients receiving continuous infusions occurs inconsistently, with surveys reporting 40 to 62% rates of compliance [38][39][40][41]. In addition, despite the perception that sedation scales are benefi cial, only 47-60% of ICUs had implemented sedation protocols at the time of the survey [39][40][41], and 85.6% of physicians in a Brazilian survey indeed believed their patients were usually over-sedated [41]. Th e same survey reported sedation levels being assessed 2 times or less per day in over 50% of patients.…”
Section: Practical Considerationsmentioning
confidence: 99%